Optimization of Reasonable Finished State for Cable-Stayed Bridge with Steel Box Girder Based on Multiplier Path Following Method - Jiapeng Shi; Yu Tao; Qingyun Xu; Jie Dai; Jin Di; Fengjiang Qin (Applied Sciences)
The increasing use of cable-stayed bridges with steel box girders necessitates more sophisticated design approaches, as the diverse environments of bridge locations place higher demands on the design process. Determining a reasonable finished state is a critical aspect of bridge design, yet the current methods are significantly constrained. A new approach to optimizing the finished state is proposed. This method’s practicality and efficiency are verified through a case study, analyzing how constraints on vertical girder deflection, horizontal pylon displacement, cable forces, and cable force uniformity affect the optimization outcome. The results show that convergence of the mixed-constraint quadratic programming model is achieved within 30 iterations, yielding an optimized finished state that meets the design criteria. The chosen constraint ranges are deemed appropriate, and the optimization method for the construction stage is thus demonstrably feasible and efficient. The multiplier path following optimization algorithm is computationally efficient, exhibiting good convergence and insensitivity to the problem size. Being easy to program, it avoids the arbitrariness of manual cable adjustment, enabling straightforward determination of a reasonable finished state for the cable-stayed bridge with a steel box girder. The vertical displacement of the main girder, the positive and negative bending moments, and the normal stresses at the top and bottom edges, as well as the positive and negative bending moments in the towers, are significantly influenced by the constraint ranges. The horizontal displacement of the pylon roof is significantly affected by the constraint ranges of both the main girder’s vertical displacement and the pylon’s horizontal displacement, while the remaining constraint ranges have a limited impact.